Educational interventions to improve screening mammography interpretation: a randomized, controlled trial - BM, Geller (AJR Am J Roentgenol, 2014)
PURPOSE: Conduct a randomized controlled trial of educational interventions to improve performance of screening mammography interpretation. MATERIALS AND METHODS: We randomly assigned physicians who interpret mammography to one of three groups: (1) self-paced DVD; (2) live, expert-led educational session; or (3) control. The DVD and live interventions used mammography cases of varying difficulty and associated teaching points. Interpretive performance was compared using a pre-/post-test design. Sensitivity, specificity, and positive predictive value (PPV) were calculated relative to two outcomes: cancer status and consensus of three experts about recall, and each were compared using logistic regression adjusting for pre-test performance. RESULTS: 102 radiologists completed all aspects of the trial. After adjustment for pre-intervention performance, the odds of improved sensitivity for correctly identifying a lesion relative to expert recall were 1.34 times higher for DVD participants than controls (95% confidence interval [CI]: 1.00, 1.81; P=0.050). The odds of improved PPV for correctly identifying a lesion relative to both expert recall (odds ratio [OR]=1.94, 95% CI: 1.24, 3.05; P=0.004) and cancer status (OR=1.81, 95% CI: 1.01, 3.23; P=0.045) were significantly improved for DVD participants compared to controls with no significant change in specificity. For the live-intervention group, specificity was significantly lower than the control group (OR relative to expert recall=0.80; 95% CI: 0.64, 1.00; P=0.048; OR relative to cancer=0.79; 95% CI: 0.65, 0.95; P=0.015). CONCLUSION: In this randomized controlled trial, the DVD educational intervention resulted in a significant improvement in mammography interpretive screening performance on a test-set, which could translate into improved clinical interpretative performance.